(3GdPgH GdEHQjR aj JaSjQ cJGH Gddg GdYRjRs - (3eMeO GdjOGdj Hf GdeNJGQ Hf eMeO SYjO GdOjeGfj,J (B1164 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg CKfGA GdcdGe Ydi bhdg JYGdi (B( (3aGMce Hjf GdfGS HGdMb hdGJJHY Gdghi ajVdc Yf SHjd Gddg (B) s
(3BNQgG (B:s
( (3ef GdLfI hGdfGS (B) (3hGdfGS YWa Ydi GdhShGS , hdjS Ydi gPG ef jhShS hGdChd CXgQ hGTgQ aGFOJGf (B: (3GdChdi (B: (3Qhi Yf GdfMZi bGd (B: (3cGf GHf eSYhO hjbhd EfgeG djS ef cJGH Gddg GdKGfjI (B: (3GdMceI ai NJe GdbQBf HGdeYhPJjf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdBjGJ ajgG HGdMeQI s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , HgG NQe s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJaSjQ hYdhe GdbQBfs